Surgical Outcome of Intradural-extra-medullarySpinal Tumour: 205 Our Experience in Dhaka Medical College & Hospital (Journal of Dhaka Medical College, 2020)
Introduction: Surgical outcome of spinal tumours varies depending on a number of factors such as: site of tumour compression within the spinal canal, the histological characteristics of tumours, the neurological progression and initial response to corticosteroid therapy, patient’s age, comorbidity, tumour extension, involvement of neighbor structures and organs etc.Materials & Methods: The 46 patients with intradural extramedullary (IDEM) spinal tumour underwent surgery by our team in 7 years (2010-2017) were reviewed retrospectively.Discussion: Analysis of the surgical outcome of our spinal tumour patients was done on different variables like age, sex, presenting symptoms, neuro imaging, comorbidities etc. The aim of surgery was decompression of the spinal cord and total removal of the tumour.Conclusion: The aim of this study is to analyze the data to make conclusion for more effective strategy as per site, size, type, resectibility and histological variety to establish an effective treatment protocol and prevention of per-operative and post-operative complications. Intradural extramedullary tumor can be radically resected with no mortality and minimal peri-operative morbidityJ Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 205-208